Pulsed Discharge Plasma in High-Pressure Environment for Water Pollutant Degradation and Nanoparticle Synthesis - Wahyu Diono; Siti Machmudah; Hideki Kanda; Yaping Zhao; Motonobu Goto (Plasma, 2021)
The application of high-voltage discharge plasma for water pollutant decomposition and the synthesis of nanoparticles under a high-pressure argon gas environment (~4 MPa) was demonstrated. The experiments were carried out in a batch-type system at room temperature with a pulsed DC power supply (15.4 to 18.6 kV) as a discharge plasma source. The results showed that the electrode materials, the pulsed repetition rates, the applied number of pulses, and the applied voltages had a significant effect on the degradation reactions of organic compounds. Furthermore, carbon solid materials from glycine decomposition were generated during the high-voltage discharge plasma treatment under high-pressure conditions, while Raman spectra and the HRTEM images indicated that titanium dioxide with a brookite structure and titanium carbide nanoparticles were also formed under these conditions. It was concluded that this process is applicable in practice and may lead to advanced organic compound decomposition and metal-based nanoparticle synthesis technologies.